Caracterização estrutural, morfológica e óptica de filmes de ZnO e Co/ZnO produzidos por eletrodeposição - Oliveira, Francisco Gilvane Sampaio de (2017)
Semiconducting films of pure and cobalt-doped zinc oxide were produced by potentiostatic electrodeposition. Pure ZnO films were produced with three reduction potentials (− 0.9 V, − 1.0 V and − 1.1 V) and for three time intervals (10 min, 30 min and 60 min). Cobalt-doped ZnO films were electrodeposited with three concentrations of cobalt in solution (5%, 10% and 15%) for 10 min and 30 min. The techniques of X-ray diffraction, scanning electron microscopy and ultraviolet-visible spectroscopy were used to study the structural, morphological and optical characteristics of the films. Results of X-ray diffraction showed that the electrodeposition process produced ZnO films with a hexagonal wurtzite-like structure in all films studied. The absence of cobalt phases in doped films indicates that doping was successful. No relevant variation was observed in the lattice parameters of the films. In all ZnO and Co/ZnO films, preferential growth is observed along the plane (0002) of the hexagonal structure. Scanning electron microscopy analyzes showed that the films have a general morphology of hexagonal nanorods. It was also verified that the reduction potentials directly influenced the morphology and thickness of the films. Energy gaps were calculated by Tauc’s method from ultraviolet-visible spectroscopy measurements. The energy gap of ZnO films decreased with increasing film thickness, regardless of time or deposition potential, due to the greater amount of crystalline defects accumulated in thicker films that introduce energy levels within the gap. Co/ZnO films deposited for 10 min showed no variation of gap as a function of cobalt concentration. In contrast, the films deposited for 30 min showed a slight gap reduction with increasing cobalt concentration, which can be attributed to the presence of cobalt ions in interstitial sites within the ZnO structure. These ions create donor states inside the gap and close to the conduction band.